Актуальні питання сучасної практики впровадження конституційної скарги в Україні: теоретико-праксеологічний аналіз - Крусян, Анжеліка Романівна; Крусян, А. Р.; Krusian, Anzhelika R. (Одеса : Гельветика, 2019)
Стаття присвячена огляду практики Конституційного Суду України щодо розгляду справ за конституційними скаргами та теоретичному аналізу конституційно-правового інституту конституційної скарги. Визначено, що інститут конституційної скарги протягом приблизно двох із половиною років залишався практично статичним в Україні. Аналіз цієї ситуації, а також перших рішень Конституційного Суду України за конституційними скаргами надав можливість висвітлити найбільш актуальні питання сучасної практики впровадженн цього інституту в реалії конституційно-правової системи України з метою визначення напрямів його функціональної ефективізації. Доведено, що великого не тільки теоретичного, але і практичного значення набуває визначення змісту законодавчих вербальних конструкцій «очевидна необґрунтованість змісту і вимог конституційної скарги» та «наявне зловживання правом на подання скарги». Резюмовано, що складання та подання конституційної скарги – це складний за формою та змістом процес, що потребує професійної правничої допомоги.

The article is devoted to the review of the practice of the Constitutional Court of Ukraine regarding the consideration of the cases on constitutional complaints and theoretical analysis of the constitutional and legal institute of constitutional complaint. It has been determined that the institute of constitutional complaint for almost two and a half years remained practically static in Ukraine. Analysis of this situation as well as the first decisions of the Constitutional Court of Ukraine on constitutional complaints, provided an opportunity to highlight the most urgent issues of the current practice of implementing this institute in the realities of the constitutional and legal system of Ukraine in order to determine the directions of its functional effectivization. It has been proved that the definition of the content of legislative verbal constructions “obvious groundlessness of content and claims of the constitutional complaint” and “existing abuse of the right to submit a complaint” acquire not only important theoretical but also practical significance. It is summarized that the drafting and filing of a constitutional complaint is a complicated by its form and content process that requires professional legal assistance.
Крусян А. Р. Актуальні питання сучасної практики впровадження конституційної скарги в Україні: теоретико-праксеологічний аналіз / А. Р. Крусян // Юридичний вісник. - Одеса : Гельветика - 2019. - № 2. - С. 13-21.
Keywords: конституційна скарга; Конституційний Суд України; конституційне провадження; права і свободи людини і громадянина; неприйнятність конституційної скарги; «очевидна необґрунтованість змісту і вимог конституційної скарги»; «наявне зловживання правом на подання скарги»; constitutional complaint; the Constitutional Court of Ukraine; constitutional proceedings; rights and freedom of man and citizen; inadmissibility of the constitutional complaint; “obvious unfoundedness of the content and requirements constitutional complaint "; " there is an abuse of the right to file a complaint "; Research Subject Categories::LAW/JURISPRUDENCE